Effects of Light Color on Growth Performance, Histomorphometric Features of Small Intestine and Some Blood Parameters in Chukar Partridges (Alectoris chukar) - Simsek, Ulku Gulcihan; Ciftci, Mehmet; Yaman, Mine; Ozcelik, Mehtap; Baykalir, Yasin; Kizilaslan, Anil; Erisir, Zeki (Kafkas Univ, Veteriner Fakultesi Dergisi, 2020)
The study was conducted in order to compare the effects of light-emitting diode (LED) light with a different color on performance parameters, histomorphometric features of the small intestine and some blood parameters in growing partridges. For this purpose, a total of 450 Chukar partridges (Alectoris chukar) were perdivided into three experimental groups including green light (GL), daylight (DL) and blue light (BL), and 250-lumen lighting. Each group contained 150 partridges with 5 repetitions per group. Experimental groups balanced according to initial live weight and raised under the same feeding and environmental conditions within the scope of the needs of partridges during 35 days. GL group showed higher live weight (P<0.05), live weight gain (P<0.01) and feed intake (P<0.05). Feed conversion and viability rates were similar among the groups (P>0.05). Higher villus height (VH), villus width, villus surface area were obtained in GL group, followed by DL and BL (P<0.001). The differences in crypt depth (CD) and VH/CD were not significant (P>0.05). Serum glucose (P<0.01) and lactate dehydrogenase levels (LDH) (P<0.05) were increased in GL groups. Serum high-density lipoprotein level (HDL) was found to be higher in DL group (P<0.01). Consequently, GL group had better results in growing partridges. GL could be utilized under intensive farming conditions for partridges.
Kınalı kekliklerde (Alectoris chukar) işık renginin büyüme performansı, ince bağırsak histomorfometrik özellikleri ve bazı kan parametreleri üzerine etkileri
Keywords: Fowl; Illumination color; Biochemical parameters; Growth performance; Histological examination